Answer:
The correct answer is s = -11.
Explanation:
To solve this problem, we must move all of the variable terms to one side of the equation and move all of the constant terms to the other side. Let's keep the variable terms on the left and move the constants to the right. Our first step will be to add 18 to both sides of the equation to cancel out the -18 on the left side:
-18 + 18 - 3s = 15 + 18
-3s = 33
Our next and final step will be to divide both sides by -3 to get the variable s completely isolated on the left side of the equation.
-3s/-3 = 33/-3
s = -11
Therefore, the correct answer is s = -11.
Hope this helps!